2019
DOI: 10.1111/rec.12929
|View full text |Cite
|
Sign up to set email alerts
|

Trait‐based approach confirms the importance of propagule limitation and assembly rules in old‐field restoration

Abstract: Community assembly theory is suggested as a guiding principle for ecological restoration to help understand the mechanisms that structure biological communities and identify where restoration interventions are needed. We studied three hypotheses related to propagule limitation, stress-dominance, and limiting similarity concepts in community assembly in a restoration field experiment with a trait-based null model approach. The experiment aimed to assist the recovery of sand grassland on former arable land in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 65 publications
1
22
0
Order By: Relevance
“…In addition, mowing affected traits related to avoidance strategies. In fact, we found that mowing promoted small-sized species (lower plant height classes, reptant strategy) [10,32] and fast growth strategies (i.e., annual life span) [34] or early flowering strategies, related to spring green and mesomorphic leaves, as stated by Catorci, et al [52] for a sub-Mediterranean climate. It was argued that species with fast growth and only sexual reproduction (absence of vegetative propagation, in the study case) complete their life cycles before the growth of the dominant species [53] and the mowing events [54].…”
Section: Effects Of Mowingmentioning
confidence: 52%
See 3 more Smart Citations
“…In addition, mowing affected traits related to avoidance strategies. In fact, we found that mowing promoted small-sized species (lower plant height classes, reptant strategy) [10,32] and fast growth strategies (i.e., annual life span) [34] or early flowering strategies, related to spring green and mesomorphic leaves, as stated by Catorci, et al [52] for a sub-Mediterranean climate. It was argued that species with fast growth and only sexual reproduction (absence of vegetative propagation, in the study case) complete their life cycles before the growth of the dominant species [53] and the mowing events [54].…”
Section: Effects Of Mowingmentioning
confidence: 52%
“…It is a non-selective disturbance [24] that, increasing light availability, promotes the survival of light-demanding seedlings, low-growth species [25,26] and germination rates of subdominant plants [27,28]. Moreover, it modifies the functional composition of plant communities by enhancing specific avoidance and tolerance strategies [29][30][31][32]. In particular, it was proven that vascular plant species richness was highest with two cuts per year, however the effect may differ in relation to the type of plant community, the timing of cutting and the biogeographic context [33].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the cover of neophytes might not decrease significantly during secondary succession (Csecserits et al, 2011) and some specialist species might not be able to establish (Molnár & Botta‐Dukát, 1998). This implies that generalist species can establish without carbon amendment, but the specialist species cannot arrive at the old‐fields without assisted dispersal (Halassy et al, 2019), and therefore the impact of carbon addition might not be detectable because of the lack of propagules of specialist species.…”
Section: Discussionmentioning
confidence: 99%